Effects of Low Intensity Blood Flow Restriction Training on Muscle Volume, Strength and Power in Healthy Middle-Aged Females - Byeong Hwan Jeon (Asian Society of Kinesiology, 2022)
OBJECTIVES The purpose of this study is to investigate the efficacy of weight training with controlled blood flow occlusion compared to conventional resistance training, in the ageing population. METHODS Twenty-three healthy female subjects (aged 40-55) were randomly assigned to one of three groups; low intensity blood flow restriction training (LI-BFRT) (n = 9), conventional resistance training (RT) (n = 7) and control (CON) (n = 7). The RT group trained between 65-70% one repetition maximum (1RM) and the LI-BFRT group trained at 30% 1RM while wearing pressure cuffs inflated to 100-120% of brachial systolic blood pressure (bSBP). Relative appendicular skeletal muscle mass (ASM/weight), isokinetic strength and power were tested pre and post 8 weeks of training. RESULTS Upper limb ASM/weight increased significantly in the LI-BFRT and RT groups (both p < 0.001). Only LI-BFRT showed significant difference compared with the CON group (p < 0.01). Lower limb ASM/weight improved in both the LI-BFRT (p < 0.01) and CON (p < 0.01) groups without group differences. Lower limb flexion strength increased in the LI-BFRT and RT groups (both p < 0.01), with differences between groups (p < 0.01, LI-BFRT > RT > CON). Only RT increased extension muscle strength (p < 0.05). Lower limb flexion and extension power improved following LI-BFRT (p < 0.05 and p < 0.01, respectively), significantly greater than RT in both flexion (p < 0.001) and extension (p < 0.01). CONCLUSIONS LI-BFRT may be as, if not more effective than RT for increasing muscle volume, strength and power in middle-aged women.